PENGARUH LATIHAN DOUBLE LEG BOX BOUND TERHADAP DAYA LEDAK OTOT TUNGKAI PADA SISWA YANG MENGIKUTI EKSTRAKURIKULER LOMPAT JAUH PUTRA SMA NEGERI 1 BENAI - Saputra, Andri; Slamet, Slamet; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Based on the results of observations that have been carried out on extracurricular students at SMA Negeri 1 Benai, problems have been found related to the leg muscle power of long jump extracurricular students. This research was conducted in the field of SMA Negeri 1 Benai, Jalan Perintis No.5 Benai, Benai District. The design of this research is pre-test post-test one group design that begins with pre-test Standing Broad Jump. In accordance with the problem to be examined, the population of this study is the extracurricular students of SMA Negeri 1 Benai, amounting to 12 people. This study uses a total sampling technique (saturated sample), in which the entire population is sampled. Based on the analysis of the t test yielded tcount of 10.88 and then compared with ttable at a significance level of 95% and df = 12-1 = 11 and ttable of 1.796 Means tcount> ttable. Furthermore, in statistical data analysis there is an average pree-test of 227.83 and an average post-test of 231.75. This means that the Double Leg Box Bound Exercise affects the Explosion Power of Leg Muscles in the Male Long Jump Extracurricular Extracurricular at SMA Negeri 1 Benai with an average difference of 3.92. Based on the findings and data processing, it can be concluded as follows: There is a significant effect of the Double Leg Box Bound (X) Exercise on the Leg Muscle Explosion Power (Y) in the Men's Long Jump Extracurricular at SMA Negeri 1 Benai.Key Words: Double Leg Bound Box, Leg Muscle Explosive Power